Patterns of play of elite badminton players - Hughes, M.; Tutton, A. (Journal of Sports Sciences, 2006)
Studying the difference in play patterns from recreational to elite players can provide useful results that can be coached back to developing female badminton players to improve their game. `Developing players` can be given feedback about the tactics of other standards of players to aid them in improving their own tactics, and elite players can gain specific feedback highlighting their opponents` game strategies, strengths and weaknesses.